2008
DOI: 10.1016/j.jacc.2008.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Levels of Serum Apolipoproteins B and A-I Predict Carotid Intima-Media Thickness and Brachial Endothelial Function in Adulthood

Abstract: Apolipoproteins B and A-I measured in children and adolescents reflect a lipoprotein profile predisposing to the development of subclinical atherosclerosis in adulthood. These markers might have value in pediatric lipid risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 41 publications
8
88
0
3
Order By: Relevance
“…Apo B and apo A-1 levels and their ratio are possibly superior to TC, HDLC and LDLC levels in terms of predicting CVD (Estonius and Kallner, 2005;Kallner and Estonius, 2006). Although there are limited data regarding the association between childhood apo B/apo A-1 ratios and long-term effects on CVD risk, they are suggested to have high predictive value in paediatric risk assessments (Frontini et al, 2008;Juonala et al, 2008). Tracking of serum lipids in Swedish children has not been reported previously, but our results are in agreement with the Finnish STRIP study (Rask-Nissila et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Apo B and apo A-1 levels and their ratio are possibly superior to TC, HDLC and LDLC levels in terms of predicting CVD (Estonius and Kallner, 2005;Kallner and Estonius, 2006). Although there are limited data regarding the association between childhood apo B/apo A-1 ratios and long-term effects on CVD risk, they are suggested to have high predictive value in paediatric risk assessments (Frontini et al, 2008;Juonala et al, 2008). Tracking of serum lipids in Swedish children has not been reported previously, but our results are in agreement with the Finnish STRIP study (Rask-Nissila et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…[9][10][11][12] We did not find an association between serum non-HDL cholesterol concentration and the dietary intake subscore of the NutriSTEP questionnaire, which is consistent with other studies involving young children that have shown an association between eating behaviours (e.g., bottle use) and iron deficiency outcomes that were independent of dietary intake (e.g., milk volume). [21][22][23] These results raise the possibility that eating behaviours are more closely related to health outcomes than dietary intake.…”
Section: Discussionsupporting
confidence: 88%
“…10,11 The Bogalusa Heart Study, which included a subgroup of children aged 2-15 years, found an association between lowdensity lipo protein (LDL) cholesterol concentration (which is highly correlated with non-HDL cholesterol) and asymptomatic atherosclerosis at autopsy. 12 The American Academy of Pediatrics recommends non-HDL cholesterol concentration as the key measure for screening for cardiovascular risk in children.…”
mentioning
confidence: 99%
“…However, the apoB/apoA-I ratio was not a better discriminatory factor between cases and controls than the total/HDL cholesterol ratio, and added little predictive power to the Framingham equation. 39 Recently, the Cardiovascular Risk in Young Finns Study 40 has demonstrated that the apoB/apoA-I ratio measured in adolescence was higher than LDL/HDL cholesterol ratio in predicting increased carotid intima-media thickness in adulthood.…”
Section: Predictive Power Of Lipoprotein Ratios For Cardiovascular Riskmentioning
confidence: 99%